Analisis Keterlaksanaan Model Pembelajaran Contextual Teaching and Learning (Ctl) dan Pengaruhnya terhadap Kemampuan Berpikir Kreatif Siswa pada Materi Laju Reaksi - Norma Rositaq; Fuldiaratman Fuldiaratman; Fatria Dewi (Journal of The Indonesian Society of Integrated Chemistry, 2017)
The aim of this research was to find out how far the implementation of CTL model and the correlation with students’ creative thinking in reaction rate materials in class XI IPA MAN Muara Bulian. This is a correlational research using mix method design. Purposive sampling technique was chosen to take the data. The instrument of this research was an observation sheet about the implementation CTL model, a students’ creative thinking sheet and a test. T-test was used to find out the influence of the implementation of CTL model and the students’ creative thinking ability. It finds out that the correlation between the implementation of CTL model and the students’ students’ creative thinking ability rxy = 0,568. It can be categorized as moderate. It also finds out that tcount > ttable (3,160 > 2,080) with dk= 23 and a = 0,05. Therefore, H0 can be rejected and H1 is accepted. It could be concluded that good implementation of CTL model tends to go with good students’ creative thinking ability and vice versa.